Identification of Determining Factors of Stunting Prevalence - Karmadani, Era Milania; Yektiningtyastuti, Yektiningtyastuti (Poltekkes Kemenkes Tanjung Karang, 2025)
Stunting is a chronic nutritional problem characterized by a toddler's height being below the standard for their age. This condition has long-term impacts on a child’s physical and cognitive development, as well as future productivity. This study was conducted to identify the determinant factors of stunting prevalence in Gunung Lurah Village, Cilongok Subdistrict, Central Java Province, Indonesia. The study employed a case-control design with a descriptive-analytic approach. The instruments used included the Kesehatan Ibu dan Anak book and questionnaires. The population in this study consisted of all mothers with toddlers in Gunung Lurah Village, totaling 648 individuals. The sample included mothers with stunted toddlers, totaling 43 (case group), and mothers with non-stunted toddlers, also totaling 43 (control group), with a 1:1 matching ratio, meaning the number of samples in the control group was equal to that in the case group. Bivariate analysis was conducted using the Chi-Square test, while multivariate analysis employed multiple logistic regression. The Chi-Square test results indicated that five out of nine factors studied had a significant association with stunting (p<0.05), namely parental knowledge (p=0.014), parenting style (p=0.004), exclusive breastfeeding (p=0.030), low birth weight (p=0.012), and socio-economic factors (p=0.001). The multiple logistic regression analysis revealed that socio-economic factors were the most significant determinant of stunting (p=0.001). This study concludes that socio-economic status is the main factor influencing the incidence of stunting. These findings are expected to serve as a basis for designing more effective programs to prevent stunting at the village level.